Study on Optimization of Infrasound Filtering Method for Coal Sample Failure under Load - Zhang, Jianguo; Wang, Man; Jia, Bing; Wang, Yujie (Frontiers in Earth Science, 2022)
Effective filtering of the infrasound signal generated by the coal samples is the basis for realizing the prediction of the infrasound of coal samples damage. Based on the infrasonic signal test of the coal samples during the loading process, a simulation method was used to construct a mixed signal containing noise signals and infrasound signals. Three methods are used to filter the mixed signal, including wavelet filtering, EMD filtering, and EMD-wavelet joint filtering. The filtering effect was compared by correlation coefficient, signal-to-noise ratio and frequency domain waveform graph. The comparison results showed that the EMD-wavelet joint filtering method had the highest correlation coefficient and signal-to-noise ratio after noise filtering, and the noise signal in the frequency domain waveform diagram was the most thorough. It provides a new method for filtering infrasound signals in the process of coal sample loading, which is great significant for improving the accuracy of infrasound prediction of coal sample damage.